The impact of psychological stress on physiological indicators in healthcare workers: a cross-sectional study - Li, Na; Wang, Yan; Dong, Yijiao; Chen, Xiaoxue; Zhang, Bin; Chen, Xianghua; Wang, Kejian; Sun, Ying (Frontiers in Public Health, 2024)
Background: Medical health workers play an essential role in the healthcare system and face unique workplace stressors. However, the impact of psychological stress on their physical health has received less attention compared to the general population.We retrospectively analyzed the Self-rating Depression Scale (SDS) questionnaires and blood testing results from 1963 medical health workers. Multivariate linear regression analysis using a backward stepwise selection strategy to identify physical examination indicators that were significantly affected by depression.Results: Depression severity, as measured by SDS index score, was positively correlated with the levels of hemoglobin (coefficient 0.0027, P = 0.0412), platelet count (coefficient 0.0005, P = 0.0198), and uric acid (coefficient 0.0004, P = 0.0492), while negatively correlated with red blood cell count (coefficient -0.0895, P = 0.0406). Similar results were observed in the subgroup analysis stratified by age and sex.Our study found a significant association between higher levels of depression and specific physiological indicators in healthcare professionals, including elevated hemoglobin, platelet counts, and uric acid levels, as well as decreased red blood cell counts. These changes in blood parameters may reflect underlying physiological stress and inflammation, potentially increasing overall health risks for healthcare workers. Addressing these physiological changes may be crucial for mitigating the health risks associated with depression. To validate our findings and develop targeted interventions, larger multi-center studies are needed to further explore the relationship between depression severity and blood parameters in healthcare professionals.